2007
DOI: 10.1038/sj.ijo.0803616
|View full text |Cite
|
Sign up to set email alerts
|

Fast food: unfriendly and unhealthy

Abstract: Although nutrition experts might be able to navigate the menus of fast-food restaurant chains, and based on the nutritional information, compose apparently 'healthy' meals, there are still many reasons why frequent fast-food consumption at most chains is unhealthy and contributes to weight gain, obesity, type 2 diabetes and coronary artery disease. Fast food generally has a high-energy density, which, together with large portion sizes, induces over consumption of calories. In addition, we have found it to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 10 publications
3
71
0
5
Order By: Relevance
“…Anwar Ul Islam; Tel: +88-0721-750071; Fax: +88-0721-711114; E-mail: profanwarulislam@yahoo.com added sugars have been proposed to link consumption of fast-food with risk of obesity. Excess caloric intake such as fast food is a well-established determinant for weight gain (Stender, 2007;Prentice et al, 2003;Isganaitis et al, 2005). In a cross-sectional study it was observed that, fast food consumption was positively associated with BMI and higher consumption of fast food at year 7 was associated with a 0.16-unit higher BMI at year 10 (Duffey et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Anwar Ul Islam; Tel: +88-0721-750071; Fax: +88-0721-711114; E-mail: profanwarulislam@yahoo.com added sugars have been proposed to link consumption of fast-food with risk of obesity. Excess caloric intake such as fast food is a well-established determinant for weight gain (Stender, 2007;Prentice et al, 2003;Isganaitis et al, 2005). In a cross-sectional study it was observed that, fast food consumption was positively associated with BMI and higher consumption of fast food at year 7 was associated with a 0.16-unit higher BMI at year 10 (Duffey et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Foods prepared outside the home are generally considered to be high in energy, saturated and trans fatty acids, total fat and salt (2) . While previous studies have investigated the nutritional quality of food provided by fast food chains, there is still a lack of data regarding the nutrient composition of meals purchased from independent takeaway outlets.…”
mentioning
confidence: 99%
“…A sound and healthy eating pattern is therefore important as it can reduce chronic morbid illnesses like obesity, coronary heart disease, hypertension, type 2 diabetes, osteoporosis, and diabetes at a later date [9][10][11][12][13][14][15][16][17]. Unfortunately, this vulnerable group is exposed to increased and frequent consumption of fast foods.…”
Section: Impact Of Excessive Fast Food Consumptionmentioning
confidence: 99%